THE IMPACT OF KNOWLEDGE ACCUMULATION OF LEADERS ON HUMAN RESOURCES MANAGEMENT PRACTICES IN NTU IRAQ - Abed Hasan Hawwasa; Fatima Jafar Habeebb (Scholars Digest Publishing, 2023)
Purpose: The aim of this study is to examine the relationship between knowledge accumulation and human resource management practices in Northern Technical University in Iraq. Theoretical framework: The knowledge accumulation represented by its dimensions (data analysis, continuous improvement, knowledge absorption, knowledge sharing and knowledge integration) as an independent variable and human resource management practices with its dimensions (human resource planning, recruitment, training and development, compensation and incentives and performance evaluation), as an dependent variable. Design/methodology/approach: In this study; We analyzed by used a quantitative approach, and 221 administrative leaders were selected as a sample and given a questionnaire. The SPSS, Ver.26 and AMOS, Ver.24 software was used to examine the data that were obtained from the questionnaire. Finding: The results showed that there is a significant correlation between knowledge accumulation and human resource management practices, in addition, there is a significant effect of accumulation knowledge on practices of human resource management. Research, Practical & Social implications: Overall, it was shown that the Northern Technical University and its formations in Nineveh Governorate is benefiting from the adopting human resources management practices by the impact of knowledge accumulation. Originality/value: Our current study attempts to bridge the research gap in the literature review about the relationship between human resources management practices and knowledge accumulation, and that the originality in the research comes from the application of these variables in the Northern Technical University and its formations in Nineveh Governorate.
Keywords: knowledge accumulation; human resources management practices; Northern Technical University; Iraq